Vitamin D Receptor Gene Polymorphisms in Childhood Brucellosis in Turkish Children - Kaman, Ayse; Öz, Fatma Nur; Sahin, Gülseren; Metin Akcan, Özge (Journal of Pediatric Infectious Diseases, 2021)
Objective The vitamin D receptor gene (VDR) polymorphisms and the risk of various infections have been studied. An association with brucellosis and vitamin D levels has been investigated but not yet with VDR gene polymorphisms. We aimed to examine the association between VDR gene polymorphisms and susceptibility to childhood brucellosis.Methods This case–control study included patients with brucellosis and healthy controls. After extracting genomic DNA using a Qiagen blood DNA isolation kit, five VDR single nucleotide polymorphisms (SNPs), including Cdx-2, FokI, BsmI, ApaI, and TaqI gene, were amplified. Genetic distribution of these SNPs of VDR gene in patient and control groups were compared.Results A total of 38 patients with brucellosis and 89 healthy controls were evaluated. The genotype distribution of Cdx2, FokI, BsmI, and ApaI polymorphisms were similar between patients and healthy controls. However, the CC homozygous genotype for VDR gene TaqI was significantly overexpressed in patients compared with controls (23.7 vs. 7.9%; p = 0.042). The frequency of the C allele of the TaqI genotype was significantly different between patients and controls (p = 0.018). On the other hand, presence of the A allele in the BsmI was associated considerably with an increased risk of brucellosis (p = 0.037). VDR polymorphism distribution was similar according to age, presence of complicated disease, and presence of bacteremia. The heterozygote TaqI polymorphism was more common in patients presented as subacute and chronic symptoms (p = 0.036).Conclusion Our results indicated the possible role in TaqI polymorphism of the VDR gene for the risk of brucellosis at the time of exposure to infection.
Keywords: brucellosis; children; vitamin D receptor gene polymorphism